A comparative study of cable fire dynamics: bench-scale experiments and numerical simulations with and without fire-retardant coating - Mishra, Raj Kumar; Tiwari, Mahesh Kumar; Dasgotra, Ankit; Sharma, Ankit; Gupta, Akhil; Meena, Mukut Kumar; Kumar, Ravi; Sharma, Pavan Kumar (Frontiers in Thermal Engineering, 2025)
Cable fires are one of the primary causes of fire hazards in nuclear power plants (NPPs) and warehouse buildings. This paper presents a study on the experimental and numerical analysis of cable failure with and without fire-resistant coating. The experiments were conducted in two sets under two different average heat fluxes, ranging from 15 (13–15) kW/ m2 to 20 (17–20) kW/ m2. A total of 10 experiments were analyzed, with five varying fire-resistant coating thicknesses from 0 to 0.8 mm for each heat flux value. For the power cable without coating, under an average heat flux value of 15 kW/ m2, the failure time was recorded as 1,897 s. Furthermore, the core and outer sheath temperatures at the time of failure, under the same heat flux, were recorded as 282.60°C and 353.90°C, respectively. For the power cable without coating under a heat flux value of 20 kW/ m2, the failure time was recorded as 991 s; the core and outer sheath temperatures at failure were recorded as 223.16°C and 310.16°C, respectively. Correlations for both heat fluxes were established, showing close agreement with experimental results—within a 2% variation. COMSOL Multiphysics software is used to perform the numerical simulations. The simulation results for the uncoated cable showed that under a heat flux value of 15 kW/ m2, the failure time, core temperature, and outer sheath temperature were 1898 s, 333.37°C, and 361.83°C, respectively. Under a heat flux value of 20 kW/ m2 for a power cable without coating, the simulation results obtained for cable failure time, core temperature, and outer sheath temperature were found to be 990 s, 212.73°C, and 256.45°C, respectively. The absolute mean deviation for the outer sheath in numerical validation was 9.94%, while for the core, it was 14.19%. The simulation results show good agreement with the experimental results. These findings contribute to a better understanding of cable burning characteristics and failure times.